Gaining practical skills in handling firearms in modern realities and under martial law - M. V. Vladymyrov; A. O. Balats; Yu. Yu. Pustovyi; V. V. Pidhayna (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The article presents the results of a scientific study, namely, the analysis of police training in firearms handling in accordance with the guidelines developed in peacetime before the beginning of Russian aggression. The author identifies the aspects that directly contribute to the selection of candidates for service in the national police, taking into account their previous experience and knowledge of firearms handling before starting their studies at higher educational institutions of the Ministry of Internal Affairs of Ukraine with specific training conditions.